Euphane and friedelane triterpenoids from Tripterygium wilfordii. (February 2022) - Li, Xiang-Mei; Yang, Cheng-Mei; Zhang, Li-Na; Jiang, Xian-Jun; Wei, Guo-Zhu; Wang, Fei
Graphical abstract: Highlights: Four new triterpenoids, including one euphane and three friedelanes from Tripterygium wilfordii were reported. The absolute configuration of C-22 of the side chain in wilfordeuphone (1 ) was established by single crystal X-ray diffraction. All of the new compounds were evaluated for cytotoxicity against five human cancer cell lines using the MTS method. Abstract: Four hitherto unknown triterpenoids, including one euphane, namely wilfordeuphone (1 ), and three friedelanes, namely wilforic acids G − I (2 –4 ), were isolated from the ethanol extract of the roots of Tripterygium wilfordii. The absolute configuration of 1 was established by single crystal X-ray diffraction. In addition, this study is the first to report euphane-type triterpenoid in the genus Tripterygium . Compound 1 exhibited the moderate cytotoxic activity when evaluated against five human cancer cell lines (HL-60, A-549, SMMC-7721, MCF-7, and SW-480), with IC50 values ranging from 14.0–26.7 μ M.